ANALISIS BELANJA MODAL DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA PADA PEMERINTAH KABUPATEN/KOTA DI INDONESIA - sugiyanta sugiyanta (Universitas Jember, 2016)
Infrastructure development is one of important aspects in achieving high economic growth of all regions in Indonesia. On the other hand, portion of capital expenditure in the budget of Local Government spending a very important component for the realization of capital expenditure undertaken local governments will have a multiplier effect to drive the regional economy. Therefore, the higher the ratio of capital spending in the budget structure, is expected to be the better its impact on economic growth. The purpose of this study was to analyze the influence of Local Independence (Local Own Source Revenue/PAD), General Purpose Grant DAU, Specific Purpose Grant (DAK), Shared Fund (DBH), Personnel Expenditures, and Surplus of Budget Financing (Silpa) in allocating of capital expenditures. Population of this research is the local goverment in Indonesia with year study period from 2011 to 2013. This study uses multiple linear regression analysis to examine the effect between variables. The result of this study shows that empirical evidence that Specific Purpose Grant and Surplus of Budget Financing has positive effects to capital expenditure. While the Local Own Source Revenue General Purpose Grant, Shared Fund, and personnel expenditures also holds negative effects to capital expendicture.